2014
DOI: 10.1038/nnano.2014.64
|View full text |Cite
|
Sign up to set email alerts
|

Atomic mechanism of the semiconducting-to-metallic phase transition in single-layered MoS2

Abstract: Phase transitions can be used to alter the properties of a material without adding any additional atoms and are therefore of significant technological value. In a solid, phase transitions involve collective atomic displacements, but such atomic processes have so far only been investigated using macroscopic approaches. Here, we show that in situ scanning transmission electron microscopy can be used to follow the structural transformation between semiconducting (2H) and metallic (1T) phases in single-layered MoS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

55
1,294
5
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,256 publications
(1,361 citation statements)
references
References 29 publications
55
1,294
5
7
Order By: Relevance
“…While the studies on the yield stress in SLMoS 2 are limited, the novel structure transition in SLMoS 2 has received considerable attention [70][71][72][73]. In this structure transition, the outer two S atomic layers are shifted relative to each other, leading to abrupt changes in the electronic and phonon properties in SLMoS 2 .…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…While the studies on the yield stress in SLMoS 2 are limited, the novel structure transition in SLMoS 2 has received considerable attention [70][71][72][73]. In this structure transition, the outer two S atomic layers are shifted relative to each other, leading to abrupt changes in the electronic and phonon properties in SLMoS 2 .…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Previous studies have shown, however, that elemental composition plays an important role in defining the physical properties of 2D materials. For example, binary systems and their alloys exhibit a variety of behaviors and modification spaces that can be optimized to meet the requirements of applications: the 1T-2H phase transition in transition metal dichalcogenides, [24][25][26][27] similar phase transitions in InSe, [28] and the structure of junctions between MoS 2 and WS 2 , [29] are but a few examples. In sharp contrast, modification methods for the properties of single elemental systems are far more limited.…”
Section: Introductionmentioning
confidence: 99%
“…13 In addition, experimentally and computationally it has demonstrated that external high pressure (~19 to 40 GPa) could induce the semiconducting to metallic transition.…”
Section: Resultsmentioning
confidence: 99%